Cancer detection rates and inter-examiner variability of MRI/TRUS fusion targeted biopsy and systematic transrectal biopsy - Zalesky, Miroslav; Stejskal, Jiri; Minarik, Ivo; Adamcova, Vanda; Babjuk, Marek; Zachoval, Roman (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2020)
BACKGROUND: Software-based MRI/TRUS fusion biopsy depends on the coordination of several steps, and inter-examiner differences could influence the results. The aim of this bicentric prospective study was to compare the detection rates of MRI/TRUS fusion targeted biopsy (TG) and systematic biopsy (SB), and the detection rates of examiners with different levels of previous experience in prostate biopsy. METHODS: A total of 419 patients underwent MRI based on a suspicion of prostate cancer with elevated PSA levels. MRI was positive in 395 patients (221 in the first biopsy group [FB] and 174 in the repeated biopsy group [RB]). A subsequent TG, followed by a SB, was performed on these patients by four different examiners. RESULTS: In the detection of clinically significant prostate cancer, a significant difference was found for TG+SB against SB in the RB group (35.1% vs. 25.3%, P=0.047). In the detection of clinically insignificant prostate cancer, the SB had a significantly higher detection rate than TG in both subgroups (FB: 11.9% vs. 4.7%, P=0.008; RB: 13.8% vs. 6.9%, P=0.034). A significant difference was found between the four examiners in the FB for TG (P=0.028), SB (P=0.036), and TG+SB (P=0.017). CONCLUSION: MRI/TRUS TG in combination with SB had significantly higher detection rates than SB in the RB group only. Differences in detection rates between examiners were dependent on the level of previous experience with TRUS guided biopsy.
Keywords: Prostatic Neoplasms; diagnostic imaging; Magnetic Resonance Imaging; nádory prostaty; palpační vyšetření konečníku; ultrazvukem navigovaná biopsie; magnetická rezonanční tomografie; intervenční ultrasonografie; Humans; biopsy; lidé středního věku; Aged; Image-Guided Biopsy; senioři; lidé; fusion; prostate cancer; Digital Rectal Examination; reprodukovatelnost výsledků; Ultrasonography, Interventional; Practice Guidelines as Topic; Male; Reproducibility of Results; Middle Aged; směrnice pro lékařskou praxi jako téma; magnetic resonance; mužské pohlaví; prospektivní studie; Prospective Studies